Affine term structure models: forecasting the Colombian yield curve (2015)
Superior modeling of the yield curve is useful for asset pricing, financial planning, and risk management. In this article, we estimate five affine term structure models using daily Colombian data. We find that a three-factor model outperforms the other models in one and five days ahead forecasts. The model’s factors closely mimic empirical proxies for the level, the slope, and the curvature of the Colombian yield curve.